2022
DOI: 10.1038/s41598-022-19607-5
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation regulates adult neurogenesis in the hippocampus in a status epilepticus animal model

Abstract: Status epilepticus (SE) refers to a single seizure that lasts longer than typical seizures or a series of consecutive seizures. The hippocampus, which is vulnerable to the effects of SE, has a critical role in memory storage and retrieval. The trisynaptic loop in the hippocampus connects the substructures thereof, namely the dentate gyrus (DG), CA3, and CA1. In an animal model of SE, abnormal neurogenesis in the DG and aberrant neural network formation result in sequential neural degeneration in CA3 and CA1. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition to this, NIR shows several neuroprotective effects in animal models with various neurological diseases such as brain stroke and Parkinson's disease [39,40]. Dysregulation of Neurogenesis is caused by the neuroinflammatory response [41], and PBM can promote neurogenesis by stimulating neural progenitor cells [42,43]. Because 830 nm PBM has the lowest absorption rate of water and hemoglobin in tissue, it has better tissue penetration in the deeper range and can reduce nerve damage [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, NIR shows several neuroprotective effects in animal models with various neurological diseases such as brain stroke and Parkinson's disease [39,40]. Dysregulation of Neurogenesis is caused by the neuroinflammatory response [41], and PBM can promote neurogenesis by stimulating neural progenitor cells [42,43]. Because 830 nm PBM has the lowest absorption rate of water and hemoglobin in tissue, it has better tissue penetration in the deeper range and can reduce nerve damage [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al. observed that tPBM could prevent seizure-induced neuronal degeneration 141 . In summary, the above studies demonstrated that tPBM with NIR light could be potential non-invasive and effective therapeutics for inhibiting epileptogenesis and alleviating epilepsy damage.…”
Section: Tpbm For Brain Diseasesmentioning
confidence: 83%
“…In addition, we indirectly demonstrated the effect of PBM on stem cell differentiation using inner ear organoids and transcriptome analysis [33]. Other published papers have also already demonstrated the proneural effects of photobiomodulation on hippocampal neurogenesis [34] and synaptic formation [35]. Therefore, it is necessary to confirm whether the fusion in application of stem cell and PBM can effectively regenerate spiral ganglion neurons.…”
Section: Introductionmentioning
confidence: 81%